Global Migration of Talent and Tax Incentives : Evidence from Malaysia's Returning Expert Program - Del Carpio, Ximena V. (World Bank, Washington, DC, 2016)
This paper presents the first evidence on the efficacy of a major program designed to encourage the return migration of high-skilled individuals. The Malaysian Returning Expert Program targets high-skilled Malaysians abroad and provides them with tax incentives to return. At several eligibility thresholds, the probability of acceptance into the program increases discontinuously. Using administrative data on applicants, the analysis is able to identify the impact of acceptance to the Returning Expert Program on the probability of returning to Malaysia. The fuzzy regression discontinuity design estimates suggest that program approval increases the return probability by 40 percent for applicants with a preexisting job offer in Malaysia. There is no significant treatment effect for those who apply without a job offer. The estimated migration elasticity with respect to the net-of-tax rate, averaged across all applicants, is 1.2. Fiscal cost-benefit analysis of the Returning Expert Program finds a modest net fiscal effect of the program, between minus $6,900 and plus $4,200 per applicant, suggesting that the program roughly pays for itself.